Eight impacts of integrating Islamic civilization insights and drawing-based approaches in developing computational understanding among primary school students - Mahiddin, Normadiah; Alias, Nursyahidah; Nasrudin, Nurhasni; Mohamed, Noraini; Mokhtar@Mother, Mazura; Tarmuji, Nor Habibah (Journal of Islamic, Social, Economics and Development, 2025)
This study investigates the impact of integrating insights from Islamic civilisation with drawing-based learning approaches on the development of computational understanding among primary school students. Recognising that children in the digital era are immersed in technology from an early age, the research emphasizes the importance of connecting technological concepts to their historical and cultural origins. Two research methods were employed: (1) motivational computing lecture sessions combined with experimental illustration-based games without gadgets, and (2) domain expert survey sessions using the Nominal Group Technique (NGT) to validate instructional design. Findings reveal that structured engagement with technological content through culturally and historically contextualised activities enhances students’ digital literacy while fostering broader cognitive and socio-emotional development. Students demonstrated improvements in analytical, logical, and visual thinking, problem-solving, creativity, and higher order thinking skills. Simultaneously, their motivation, autonomy, and collaboration abilities were strengthened, reflecting gains in soft skills and overall character development. Incorporating perspectives from Islamic civilisation situates computational learning within an authentic intellectual heritage, enriching students’ appreciation of the evolution of science and technology while promoting holistic understanding and critical reflection. Overall, the study highlights the pedagogical effectiveness of combining historical, cultural, and visualisation-based strategies in primary education. Integrating civilisational insights with drawing-based learning not only supports computational understanding but also cultivates creativity, discipline, and sustained engagement, producing students who are both digitally competent and equipped with critical and creative thinking skills.